Development of bouillon cubes from souari nut pulp: formulation and physicochemical and sensorial evaluations - Rodrigues,Érica de Fátima (2016)
Summary The proximate composition and acceptability of bouillon cubes prepared from souari nut pulp flour were evaluated. The whole fruit pulp and formulated bouillon cubes were subjected to an analysis of the total phenolic compounds, protein, lipid, moisture, ash, fibre, total carbohydrate and total energy values. The selected formulations of souari nut bouillon cubes were subjected to a sensory analysis as seasoning for rice preparations, and the physicochemical analysis of the most widely preferred formulation was carried out. The whole souari nut pulp was found to contain 44.4% moisture, 37.7% lipids, 2.1% protein and 10.9% total carbohydrates, as well as 324 mg of total phenolic compounds per 100 g of pulp. The souari flour contained 9.8% moisture. In the sensory tests, the preferred formulation was that containing the highest souari nut flour concentration. This formulation contained 8.4% moisture, 52.3% lipids, 3.1% protein, 19.4% total carbohydrate, 321 mg of phenolic compounds per 100 g and a total energy value of 560.7 kcal per 100 g. The souari nut bouillon cubes presented the characteristic colour, taste and aroma of the fruit and an appearance similar to that of commercial bouillon cubes.